David Clutterbuck, Mentoring and Coaching - Jenkins, S. (International Journal of Sports Science and Coaching, 2013)
David Clutterbuck is a prolific writer on management and business, who is also a thought leader, advocate and visionary in mentoring. He has distinguished between the traditional US sponsorship-based model of mentoring which emphasizes the use of the mentor's power, influence and authority on behalf of a protégé and the European, development-based model of mentoring which emphasizes the mentor's experience and wisdom to enable the mentee to become self-reliant and to take ownership of their personal and professional development. In order to stimulate commentaries from his peers in the world of mentoring, as well as stakeholders of mentoring in the world of sport, this article presents selected aspects of Clutterbuck's work on mentoring, such as formal vs. informal mentoring, mentoring vs. coaching, conversation, goals, and trends. A theme that runs through the article is the influence of Peter Drucker on Clutterbuck.